2016
DOI: 10.1097/md.0000000000004879
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for chronic obstructive pulmonary disease (COPD)

Abstract: Background:Acupuncture has been suggested to treat chronic obstructive pulmonary disease (COPD) in China. However, current evidence is insufficient to draw a firm conclusion regarding the effectiveness of acupuncture in COPD. Therefore, this multicenter, randomized, sham-controlled study was designed to evaluate the efficacy of acupuncture for treating patients with COPD.Methods:This is a two-arm, parallel group, multicenter, randomized, sham-controlled trial with concealed allocation, and participants, assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 32 publications
(29 reference statements)
0
43
0
Order By: Relevance
“…Five studies [ 8 , 10 , 11 , 17 , 18 ] provided numerical data for SGRQ total scores and were included in the meta-analysis. Analysis of the data indicated that there was heterogeneity ( χ 2 = 39.18, P < 0.00001; I 2 = 90%); hence, a random-effect model was used.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [ 8 , 10 , 11 , 17 , 18 ] provided numerical data for SGRQ total scores and were included in the meta-analysis. Analysis of the data indicated that there was heterogeneity ( χ 2 = 39.18, P < 0.00001; I 2 = 90%); hence, a random-effect model was used.…”
Section: Resultsmentioning
confidence: 99%
“…[31] Actually, AT has been used to treat patients with COPD in China. [32] Although the mechanism in still unclear, results of clinical studies indicates that AT has a comparable effect to the medication treatment on patients with moderate to severe COPD and it is safe with few side effects. [33] We hope this systematic review will provide more reliable evidence to help patients and clinicians in the management of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Since the deep site of the acupoint Futu (LI-18) is in the neighborhood of C2-C4 nerves, we consider that stimulation applied to LI-18 would activate the sternocleitomastoid muscles. Acupoint LI-18 has been used, together with other acupoints which have specific application in three clinical studies to treat COPD patients [57] [58] [59]; the consequence of acupuncturing the other acupoints have been explained in section (12.2) of our very recent study [18]. When the superior muscle fibers of the trapzius contract, they help to raise the rib cage, and the superior part is an inspiratory muscle.…”
Section: Four Important Muscles Of Inspiration-the Scalene Muscles Inmentioning
confidence: 99%